Influence of type of metal alloy and penetration limit in determining the working length with two apex locators (Research, Society and Development, 2022)
This ex vivo study aimed to evaluate the precision of two electronic foramen locators (Root ZX mini and RomiApex A15) inserting the manual Flexofile or NiTi endodontic files until reaching the apical foramen or surpassing it. Sixty mesial root canals of mandibular molars were selected. Root canal real length measurement and odontometry were performed after the access cavity surgery, cervical pre-flaring, and apical preparation. The precision of the electronic foramen locators was verified at each instrumentation phase, comparing the electronic measurements with the real length. The 3-way ANOVA test was used to evaluate the error of electronic measurements, and a significance level was set at 5%. At the first odontometry, the RZX was significantly more precise than the A15 (p